2018
DOI: 10.1080/10253890.2018.1484099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute alarm odor exposure and biological sex on generalized avoidance and glutamatergic signaling in the hippocampus of Wistar rats

Abstract: Post-traumatic stress disorder (PTSD) is characterized by the development of paradoxical memory disturbances including intrusive memories and amnesia for specific details of the traumatic experience. Despite evidence that women are at higher risk to develop PTSD, most animal research has focused on the processes by which male rodents develop adaptive fear memory. As such, the mechanisms contributing to sex differences in the development of PTSD-like memory disturbances are poorly understood. In this investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 75 publications
2
6
0
Order By: Relevance
“…TMT elicits innate fear and stress-related behavioral responses including freezing [34,40], immobility [27]; [36] and avoidance behavior [27]; [35,36,41]. Here, bedding was present in the TMT exposure context so that we could examine an additional stress-reactivity behavior, defensive digging [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMT elicits innate fear and stress-related behavioral responses including freezing [34,40], immobility [27]; [36] and avoidance behavior [27]; [35,36,41]. Here, bedding was present in the TMT exposure context so that we could examine an additional stress-reactivity behavior, defensive digging [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is interpreted as a proactive response to stress [29][30][31], such that it reflects an active coping response or fear-related behavior [32] and predator-stress responsiveness [33]. Freezing behavior is a wellcharacterized fear-like behavior that animals have been shown to engage in during TMT exposure [27,[34][35][36]. The present study sought to examine individual differences in stress-reactive behaviors (digging and immobility) during TMT exposure in male and female Long Evans rats to determine whether these individual differences could predict subsequent increases in context reactivity, hyperarousal and anxiety-like behavior and alcohol self-administration.…”
Section: Introductionmentioning
confidence: 99%
“…It is interpreted as a proactive response to stress [29][30][31], such that it reflects an active coping response or fear-related behavior [32] and predator-stress responsiveness [33]. Freezing behavior is a wellcharacterized fear-like behavior that animals have been shown to engage in during TMT exposure [27,[34][35][36]. The present study sought to examine individual differences in stress-reactive behaviors (digging and immobility) during TMT exposure in male and female Long Evans rats to determine whether these individual differences could predict subsequent increases in context reactivity, hyperarousal and anxiety-like behavior and alcohol self-administration.…”
Section: Introductionmentioning
confidence: 99%
“…In view of molecules that stimulate the olfaction, 2,5-dihydro-2,4,5-trimethylthiazoline (TMT) is the main component of fox feces. Therefore, TMT is a predator odor for rodents, and it causes PTSD as a serious stressor [ 13 , 18 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. Miyazono et al [ 75 ] found that a mixture of three pyrazine analogues (P-mix) present at high levels in wolf urine induced fear-related responses in mice, which was attenuated by etizolam, an anxiolytic.…”
Section: Olfaction and Stress Response In The Brainmentioning
confidence: 99%
“…They suggested that this odor may be involved in 4-methylpentanal and hexanal. On the response to odor stress, gender differences are pointed out [ 13 , 18 , 70 , 78 , 79 ]. Harris et al [ 80 ] demonstrated the social defeat paradigm that works in female mice.…”
Section: Olfaction and Stress Response In The Brainmentioning
confidence: 99%